A multiplex polymerase chain reaction (mPCR) assay for detection of salmonella typhi and salmonella paratyphi A - Daun, Kenny AK (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Typhoid and paratyphoid fever, caused by the bacteria Salmonella Typhi and Salmonella Paratyphi A still remain major health problems worldwide. Both of these bacteria infect only human and cause systemic disease through fecal oral route. Culture and serological methods are used for diagnosis of typhoid and paratyphoid fever but the methods are laborious and produce results from 2-7 days. Thus, the study aims to develop multiplex polymerase chain reaction (mPCR) assay for specific detection of ST50 gene and spa4289 gene for S. Typhi and S. Paratyphi A respectively. Genomic DNA was extracted using commercial Qiagen DNA extraction kit. Gradient PCR was performed with the annealing temperature ranging from 50°C-70°C. The analytical sensitivity of mPCR was determined using DNA concentration of 50 ng - 10 pg. Seventy five bacterial isolates (25 of S. Typhi, 25 of S. Paratyphi A and 25 of Salmonella serovars and other enteric bacteria) were used for evaluation of this study. PCR was performed at initial denaturation at 94°C for 2 minutes followed by 30 cycles of denaturation at 94°C for 30 sec, annealing at 63°C for 30 sec and elongation at 72°C for 1 min with a final additional elongation at 72°C for 10 min. Positive result was detected with the presence ofPCR amplicon size of 1238 bp for S. Typhi and 549 bp for S. Paratyphi A when analyzed via agarose gel electrophoresis. As a result, the optimized annealing temperature of the multiplex PCR was 63°C with the detection limit of 0.39 ng when both S. Typhi and S. Paratyphi were used as DNA template. Furthermore, mPCR was capable to detect 3.13 ng for S. Typhi and 0.19 ng for S. Paratyphi A when analytical sensitivity test was performed using serially diluted DNA. The evaluation study with DNA from 75 bacterial isolates showed sensitivity and specificity of 100%. As an alternative to conventional culture method, multiplex PCR based on ST50 and spa4289 (hsdM) has the potential to be used as diagnostic tools for rapid detection of S. Typhi and S. Paratyphi A.